Currency Translation and Performance Evaluation in Multinationals. (Book Review). - Meyer, Philip E.; Bindon, Kathleen J. (The Accounting Review, 1981)
Reviews the book "Currency Translation and Performance Evaluation in Multinationals," by Helen Gernon Morsicato.